The Influence of E-Tax Services, Income and Communication Style on Tax Compliance - Saryono Putri, Nany; Daito, Apollo (Dinasti Publisher, 2021)
This study aims to determine what factors affect taxpayer compliance. The variables to be studied are e-tax services, income level, and communication style. The sample of this research is 88 individual taxpayers (WPOP) in the city of Tangerang. Data collection was carried out by distributing questionnaires to the WPOP. The data that has been obtained is tested using the second order method with the help of the SmartPLS program. The overall results of this study indicate that e-tax services have a significant effect on taxpayer compliance, with the level of income and communication styles not having a significant effect on taxpayer compliance. This study has limitations, namely the sample used is less than 100 samples. Keywords: e-tax services, income, communication style, tax compliance, individual taxpayers.